Novel design and performance of the solidly mounted resonator with an AlN-buffered ZnO piezoelectric film. (August 2018) - Liu, Yijian; Li, Zhongli; Yang, Zhi; Su, Yanjie; Zhang, Yaozhong; Hwang, Huey-liang; Duan, Franklin; Zhang, Yafei
Abstract: In this report, an AlN-buffered ZnO double-layer piezoelectric layer based SMR (solidly mounted resonator) was designed and fabricated, in which the nano AlN film acted as a buffer layer. For optimization of the piezoelectric layer, a series of SMRs were fabricated with different AlN layer thicknesses from 15 nm to 100 nm by radio-frequency magnetron sputtering (RFMS). Optimization of the AlN-buffered ZnO thin films for the SMR devices performance were investigated through XRD (X-ray diffraction), SEM (Scanning electron microscopy), AFM (atomic force microscope) and NWA (network analyzer) with the different AlN layer thickness. From the investigations, we concluded that existence of nano AlN layer obviously affected the resonant performance of the ZnO based SMR device and it was found that the best ZnO thin film was exhibited when AlN thickness was 55 nm which shows better return losses and higher Q factor than devices exhibiting an effective method to optimize ZnO SMR. Highlights: XRD patterns and morphology of the films were investigated via changing the thickness of AlN buffer layer. The SMR device based on AlN-buffered ZnO layer was proposed and fabricated. The optimization of AlN buffer thickness on the performance of ZnO SMR device. An effective optimization method where the SMR device with 55nm AlN buffer layer shows better performance.